(untitled) (Sebha University Conference Proceedings, 2025)
The increasing need for durable and cost-effective road infrastructure has led to a growing interest in the role of mineral fillers in enhancing asphalt mixture performance. This study investigates the influence of different filler content levels—1.5%, 5.3%, and 12% by total mix weight—on the mechanical and durability properties of Hot Mix Asphalt (HMA). The primary objective is to identify the optimal filler proportion that enhances pavement strength, moisture resistance, and rutting performance.To achieve this, laboratory testing was conducted using standardized procedures, including the Marshall Stability and Flow test (ASTM D6927; AASHTO T 245), Hamburg Wheel Tracking test (AASHTO T 324), and Indirect Tensile Strength test (AASHTO T 283). Limestone powder was used as the mineral filler across all mixtures. The results showed that asphalt mixtures containing 5.3% filler provided the best balance of mechanical strength and resistance to moisture-induced damage and deformation. Mixtures with 1.5% filler had excessive air voids and low cohesion, while 12% filler led to stiffness-related cracking and rutting under simulated loading. These findings emphasize the importance of optimizing filler content for improved pavement performance and service life. The results can guide transportation engineers and policymakers in developing more durable, sustainable, and economically efficient roadways. Future research may explore eco-friendly alternative fillers and long-term field validation.